Retour sur l’identification de la Naturalis historia de Pline l’Ancien corrigée par Robert de Torigni - Elisa Lonati (Tabularia)
In 2007, Michael D. Reeve proposed to identify the manuscript Le Mans, Médiathèque Louis-Aragon, 263, a beautiful 12th-century witness of Pliny the Elder’s Naturalis historia, with the codex kept at the Mont Saint-Michel between the middle of the 12th century – when it was brought there and corrected by the famous abbot Robert of Torigni – and the end of the 17th century; instead, Patricia Stirnemann presented it as made for English patrons and by English artisans working on the continent, very likely at Le Mans. After a critical review of these assumptions, we develop a palaeographic analysis of the hand that corrected Le Mans 263 a few years after its execution, in order to see if it is identifiable with abbot Robert’s hand on the basis of the descriptions recently given by Benjamin Pohl, Stéphane Lecouteux and Thomas N. Bisson. At the same time, we try to give an overview on the Naturalis historia’s circulation during the High Middle Ages between Paris, Normandy and England, showing how the framework is more challenging than previously thought.